193 Delayed Resolution of Syrinx After Posterior Fossa Decompression Without Dural Opening in Children With Chiari I Malformation. (August 2015) - Kennedy, Benjamin C.; Nelp, Taylor B.; Kelly, Kathleen M.; Phan, Michelle Q.; Bruce, Samuel S.; McDowell, Michael Maurice; Feldstein, Neil; Anderson, Richard C.E.
Abstract : INTRODUCTION: Chiari Malformation Type I (CM-I) is associated with syrinx in 25% to 85% of patients. Although posterior fossa decompression (PFD) without dural opening is an accepted treatment option for children with symptomatic CM-1, many surgeons prefer to open the dura if syrinx exists. The purpose of this study was to investigate the frequency and timing of syrinx resolution in children undergoing PFD without dural opening for CM-1. METHODS: A retrospective review was conducted of 68 consecutive pediatric patients with CM-I and syringomyelia who underwent PFD without dural opening. Patient demographics, presenting symptoms and signs, radiographic findings, and intraoperative ultrasound and neuromonitoring findings were studied as well as the patients' clinical and radiographic follow-up. RESULTS: During the mean radiographic follow-up period of 32 months, 70% of the syringes improved. Syrinx improvement occurred at a mean of 31 months postoperatively. All patients experienced symptom improvement within the first year, despite only 26% of patients showing radiographic improvement during that period. Patients presenting with sensory symptoms or motor weakness had a higher likelihood of having radiographic syrinx improvement postoperatively. CONCLUSION: In children with CM-I and syrinx undergoing PFD without dural opening, syrinx resolution occurs in approximately 70% of patients. Radiographic improvement of the syrinx is delayed, but does not correlate temporally with symptom improvement. Sensory symptoms or motor weakness on presentation are associated with syrinx resolution after surgery.